Swift ren gong zhi neng shi zhan : cong ji chu li lun dao AI qu dong de ying yong cheng xu kai fa = Practical artificial intelligence with Swift - Geldard, Mars; Manning, Jon; Buttfield-Addison, Paris; Nugent, Tim (O'Reilly jing pin tu shu xi lie., 2021)
Detailed summary in vernacular field,